2016
DOI: 10.1080/09593330.2016.1271020
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic wastewater treatment by the ZVI/H2O2 process

Abstract: The ZVI/HO process was applied for cosmetic wastewater treatment. Two commercial zero-valent iron (ZVI) types with different granulations were chosen: Hepure Ferrox PRB and Hepure Ferrox Target. In addition, the pH and stirring method influence on ZVI/HO process efficiency was studied. During the ZVI and ZVI/HO processes, linear Fe ions concentration increase was observed. The addition of HO significantly accelerated the iron dissolution process. The highest COD removal was obtained using finer ZVI (Hepure Fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
0
12
0
2
Order By: Relevance
“…In the second stage the homogeneous Fenton reaction occurred in the presence of leached Fe, with enhancement of degradation because of the synergistic effect between Fenton reaction and reduction by ZVI-K [13]. A study on cosmetic wastewater treatment with ZVI showed that, while COD removal <15% was obtained by using ZVI or H 2 O 2 alone, the ZVI-Fenton process (ZVI + H 2 O 2 ) removed 84% of COD after 120 min [6]. Likewise, Segura et al have applied the ZVI-Fenton process for the treatment of drug manufacturing plant wastewater [3], achieving 60% of TOC mineralization.…”
Section: Zero Valent Ironmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second stage the homogeneous Fenton reaction occurred in the presence of leached Fe, with enhancement of degradation because of the synergistic effect between Fenton reaction and reduction by ZVI-K [13]. A study on cosmetic wastewater treatment with ZVI showed that, while COD removal <15% was obtained by using ZVI or H 2 O 2 alone, the ZVI-Fenton process (ZVI + H 2 O 2 ) removed 84% of COD after 120 min [6]. Likewise, Segura et al have applied the ZVI-Fenton process for the treatment of drug manufacturing plant wastewater [3], achieving 60% of TOC mineralization.…”
Section: Zero Valent Ironmentioning
confidence: 99%
“…Moreover, the reaction is fast and requires easy-to-use reagents [5]. The Fenton process can be applied either to decontaminate wastewater so that it meets the standards for safe discharge into natural water bodies, or to minimize the effluent toxicity and enhance its biodegradability, thereby allowing for an efficient biological depuration in municipal wastewater treatment plants [6]. In the classic homogeneous Fenton process, strong oxidant species are primarily produced by reaction of H 2 O 2 with iron ions (Fe 2+ ) in acidic conditions [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changing the stirring method from magnetic into a mechanic one could result in a decrease in process efficiency because of the paramagnetic properties of oxygen. Under the magnetic stirrer, the magnetic field increased the treatment efficiency [56,57]. It was also proved that radical generation is higher in oxic conditions [50], with a bigger amount of dissolved oxygen [58], or with more intensive stirring [53].…”
Section: Fe 0 /H 2 O 2 Processmentioning
confidence: 93%
“…In addition, the inuences of several surrounding media on the PL characteristics of these nanowires have been studied and it is observed that the red PL emission is sensitive to H 2 O 2 , a reactive oxygen species, at low concentrations. H 2 O 2 is used in a wide range of applications, such as disinfectant, antiseptic and oxidizer in food, 25 pharmaceutical, 26 biomedical, 27 cosmetic, 28 and chemical industries, involving biological and environmental implications. 29,30 Besides, it is a propellant in rockets, 31 and a precursor and a decomposition product of triacetone triperoxide, a progressively used explosive by terrorists.…”
Section: Introductionmentioning
confidence: 99%